Comprehensiveness of infant formula and bottle feeding resources: A review of information from Australian healthcare organisations - Heilok Cheng; Chris Rossiter; Donna Size; Elizabeth Denney‐Wilson (Wiley, 2022)
Abstract The use of infant formula is widespread internationally. In Australia, 55% of infants receive formula before 6 months of age, with higher rates among disadvantaged communities. Infant formula use can contribute to childhood overweight and obesity, through formula composition and feeding behaviours, such as adding cereal to bottles and parental feeding style. While information abounds to promote and support breastfeeding, formula‐feeding parents report a paucity of advice and support; many rely on formula packaging for information. This study systematically searched and reviewed online resources for infant formula and bottle feeding from Australian governments, health services, hospitals, and not‐for‐profit parenting organisations. A comprehensive search strategy located 74 current resources, mostly for parents. Researchers evaluated the resources against best practice criteria derived from Australian government and UNICEF guidelines on six topics. They assessed how comprehensively the resources addressed each topic and whether the resources provided all the information necessary for parents to understand each topic. The mean 'comprehensiveness' rating for topics across all resources was 54.36%. However, some topics were addressed more fully than others. Information on 'discussing infant formula with health workers' and on 'preparing infant formula' was more frequently accurate and comprehensive. However, there was much less comprehensive information on 'using infant formula', including amounts of formula to feed, use of bottle teats, appropriate bottle‐feeding practice and responsiveness to infant satiety cues. Over half the resources were written at an acceptable reading level.